On A-statistical convergence and A-statistical Cauchy via ideal
In [Analysis 1985, 5 (4), 301-313], J.A. Fridy proved an equivalence relation between statistical convergence and statistical Cauchy sequence. In this paper, we define A^I^* -statistical convergence and find under certain conditions, that it is equivalent to A^I-statistical convergence defined in [Appl. Math. Lett. 2012, 25 (4), 733-738]. Moreover, we define A^I- and A^I^* -statistical Cauchy sequences and find some equivalent relation with A^I- and A^I^* -statistical convergence. , number=2, journal=Carpathian Mathematical Publications, author=Edely, O.H. and Mursaleen, M., year=2022, month=Dec., pages=442–452